Cardiac Abnormalities in Adult Patients With Polymyositis or Dermatomyositis as Assessed by Noninvasive Modalities. Issue 7 (July 2016) - Diederichsen, L. P.; Simonsen, J. A.; Diederichsen, A. C.; Hvidsten, S.; Hougaard, M.; Junker, P.; Søndergaard, K.; Lundberg, I. E.; Tvede, N.; Sandgaard, N. C. F.; Christensen, A. F.; Dreyer, L.; et al.
Abstract : Objective: Cardiac events are a major cause of death in patients with idiopathic inflammatory myopathies. The study objective was in a controlled setting to describe cardiac abnormalities by noninvasive methods in a cohort of patients with polymyositis (PM) or dermatomyositis (DM) and to identify predictors for cardiac dysfunction. Methods: In a cross‐sectional study, 76 patients with PM/DM and 48 matched healthy controls (HCs) were assessed by serum levels of cardiac troponin I, electrocardiography, Holter monitoring, echocardiography with tissue Doppler imaging, and quantitative cardiac 99m Tc‐pyrophosphate ( 99m Tc‐PYP) scintigraphy. Results: Compared to HCs, patients with PM/DM more frequently had left ventricular diastolic dysfunction (LVDD) (12% versus 0%; P  = 0.02) and longer QRS and QT intervals ( P  = 0.007 and P < 0.0001, respectively). In multivariate analysis, factors associated with LVDD were age ( P  = 0.001), disease duration ( P  = 0.004), presence of myositis‐specific or ‐associated autoantibodies ( P  = 0.05), and high cardiac 99m Tc‐PYP uptake ( P  = 0.006). In multivariate analysis of the pooled data for patients and HCs, a diagnosis of PM/DM ( P < 0.0001) was associated with LVDD. Conclusion: Patients with PM or DM had an increased prevalence of cardiac abnormalities compared to HCs. LVDD was a common occurrence in PM/DM patients and correlated to disease duration. In addition, the association of LVDD with myositis‐specific or ‐associated autoantibodies and high cardiac 99m Tc‐PYP uptake supports the notion of underlying autoimmunity and myocardial inflammation in patients with PM/DM.